Leishmania (Viannia) naiffi : rare enough to be neglected? - Silva, Giselle Aparecida Fagundes (2015)
In the Brazilian Amazon, American tegumentary leishmaniasis (ATL) is endemic and presents a wide spectrum of clinical manifestations due, in part, to the circulation of at least seven Leishmaniaspecies. Few reports of Leishmania (Viannia) naiffiinfection suggest that its occurrence is uncommon and the reported cases present a benign clinical course and a good response to treatment. This study aimed to strengthen the clinical and epidemiological importance of L. (V.) naiffiin the Amazon Region (Manaus, state of Amazonas) and to report therapeutic failure in patients infected with this species. Thirty Leishmania spp samples isolated from cutaneous lesions were characterised by multilocus enzyme electrophoresis. As expected, the most common species was Leishmania (V.) guyanensis (20 cases). However, a relevant number ofL. (V.) naiffi patients (8 cases) was observed, thus demonstrating that this species is not uncommon in the region. No patient infected withL. (V.) naiffievolved to spontaneous cure until the start of treatment, which indicated that this species may not have a self-limiting nature. In addition, two of the patients experienced a poor response to antimonial or pentamidine therapy. Thus, either ATL cases due to L. (V.) naifficannot be as uncommon as previously thought or this species is currently expanding in this region.